The wimpy kid movie diary how Greg Heffley went Hollywood - Kinney, Jeff (Puffin Books, an imprint of Penguin Random House Group London, 2012)
Presents a behind-the-scenes look at the making of the motion pictures "Diary of a Wimpy Kid," "Diary of a Wimpy Kid: Roderick rules," and "Diary of a Wimpy Kid: Dog days," offering script pages, storyboard sketches, costume designs, and original art